Effect Work Discipline, Leadership and Motivation on Staff Performance in West Java Province Regional Development Office - Achmad Rizal; Emma Rochima; Mudiyati Rahmatunnisa; Cipta Endyana (Forum Inovasi Bisnis dan Manajemen, 2020)
The performance was the result that was the goal in every organization to achieve its goals. Human resources have a vital position, considering its human resources' quality strongly influences the organization's performance. Besides, high-quality natural resources were useful in adjusting the movement of business climate change so quickly. Work discipline, leadership, and motivation were essential for a company to increase staff performance. This study aims to determine work discipline, leadership, and motivation on staff performance—associative research method with multiple linear analysis techniques. The study population amounted to 150 respondents; the sampling technique used purposive sampling, where the number of samples of 60 respondents was calculated using the Slovin formula. The study results show that simultaneously work discipline, leadership, and motivation significantly influence staff performance. Partially only work discipline and leadership have a significant effect, while a lack of motivation was significant for staff performance. As one of the determinants of direction and organizational goals, leaders should control work behaviors and direct them to staff job satisfaction.